Factors influencing the sustainability of family owned business and the role of role conflict as a mediator - Ansarutheen bin Mohiadeen Abdul Kader
This study focuses on the succession of family business in the Klang Valley in Malaysia. It looks into the extent of succession, family relationship, role conflict, and sustainability of these family businesses, and it examine the influence of succession, family relationship and role conflict on the business sustainability. Family businesses comprise 70% of Malaysian businesses, yet the attrition rate from one generation to another is alarming. Only one-third survive the transition to the second generation and only 13% survive to the third generation. The study, therefore, aims at establishing an underlying structure of business sustainability, and thereafter, validated the psychometric properties of the four main factors (succession, family relationship, role conflict, and sustainability) scales and measurement model. A total of 480 business men and women (266 females and 214 males) from Klang valley, Malaysia participated in the survey. An adapted questionnaire with 101 items measured on a 5-point Likert scale was used. The data were then analysed using Exploratory Factor Analysis to explore the underlying dimensions, Confirmatory Factor Analysis to test the measurement models, and Structural Equation Modelling to explore the function of role conflict as an influencer on the sustainability of a family business. The EFA extracted four underlying dimensions for this study, with a variance explained of 65.96% of the variance in the data were finally retained. The CFA confirmed that the four measurement models are valid and reliable provided evidence for the convergent and discriminant validity, and composite reliability of the scales. The SEM results explained a causal relationship between succession and family relationship and sustainability of business mediating by role conflict. The results suggest that role conflict is a likely influencer of sustainability of business. This study has shown that succession plays an important factor in sustainability of family owned businesses. Succession planning should not be stand alone, it should be paired with succession management which focuses on continuing daily efforts to build talent and may include the managerial role in coaching, giving feedback and helping individuals realize their potentials. Family businesses are fertile environment for conflict and conflict stimulates disequilibrium in the organization and if not addressed, can bring about dysfunctional revolutionary change in the family business. The ability to forecast potential areas of conflict in the family business is one of major contributions of a life cycle approach to the growth of the organization. If the family owned businesses managed to reduce tension in their businesses, their revenue would increase by billions annually.